Rancang Bangun Mesin Pembuat Briket Arang Sabut Kelapa Semi Otomatis - Priyambada, Sashatta Daniela; Abdi, Ferly Isnomo; Sakti, Arya Mahendra; Ganda, Andita Nataria Fitri; Tsamroh, Dewi ‘Izzatus (Universitas Negeri Surabaya, 2024)
Indonesia is a tropical country with many coconut trees (cocos nucifera). Coconut fiber is currently only a waste that cannot be utilized. We can utilize it into charcoal briquettes. The utilization of charcoal briquettes is one of the solutions in exploring alternative energy sources and reducing environmental pollution. In general, the briquette production process is carried out with three different machines, namely a mixer, an extruder, and a cutting machine. This research aims to design and test the function of a semi automatic coconut fiber charcoal briquette making machine. The research method used is Research and Development (R&D). The results of this study obtained frame dimensions of 700 mm x 270 mm, extruder tube length of 500 mm with a diameter of 100 mm, shaft length of 550 mm with a diameter of 25 mm, using a ½ HP AC electric motor with a speed of 1400 RPM, 3 inch and 4 inch pulleys, speed reducer WPA 40 ratio of 1 : 20, briquette mold 30 mm x 30 mm x 30 mm. The test found that the best capacity and rotation for the coir charcoal briquette making machine is by using a 4 inch pulley variation with an average printing capacity of 7,3 kg/hour and a rotation speed of 94,7 RPM, so the larger the pulley used the faster the rotation speed and the capacity of the printing results is also faster. Keywords: Charcoal Briquette, Coconut Coir, Semi Automatic, Briquetting Machine